Relationship between Transformational Leadership and Church Health: A Survey of Selected Denominational Churches in Nairobi City County, Kenya - Muthuku, Mwongeli; Oginde, David; Chiroma, Nathan (European Scientific Journal, ESJ, 2023)
The subject of church health and its deteriorating condition has taken center-stage in leadership discourse across the world. A decline in the health of a church has negative implications not only on the sustainability of the church but also on the wider society owing to the role of the church as the moral custodian of society. An argument has been advanced in extant scholarship that transformational leadership is suitable for guiding religious organizations. However, most studies on this front take focus almost exclusively on the numerical health aspect of the organizations. The aim of the present study was to estimate the differential effect of transformational leadership on spiritual health and economic health in addition to the numerical health of selected churches in Nairobi City County, Kenya. The target population comprised members of selected denominational churches from which a sample size of 330 members was drawn. The participants filled out the Multifactor Leadership Questionnaire and the Natural Church Development tools. Data analysis was done using SPSS. Results showed that the four transformational leadership dimensions explained 40% of numerical health metrics, 56.9% of economic health metrics, and 50.2% of spiritual health metrics. The conclusion was drawn that transformational leadership had a positive but differential effect on church health dimensions. The study has affirmed the relevance of transformational leadership in enhancing the numeric, economic, and spiritual health of the church in Kenya. However, in as much as the effect sizes were large, a substantial share of church health metrics still remained unexplained, thereby providing grounds for continued empirical inquiry.